Synthesis and Characterization of Biodiesel from Coconut Oil Using Renewable ZnO/CaO-CA Catalyst with Microwave Heating - Surya Julius Sembiring; Lisnawaty Simatupang; Jhony Hartanta Sembiring; Elfrida Ginting (Jurnal Kimia Riset, 2026)
Biodiesel is a type of liquid fuel produced from vegetable oil and has combustion properties similar to diesel fuel, which is processed through esterification-transesterification as an alternative to fossil fuels. This study aims to optimize the esterification-transesterification process by examining the effect of time on the conversion of coconut oil into biodiesel based on the suitability of SNI 7182-2015. The methodology used involves microwave heating. Biodiesel is synthesized using CaO catalyst derived from fish bone waste impregnated with ZnO and activated carbon support. Catalyst preparation is carried out through impregnation, followed by calcination at 500℃. The characterization of the ZnO/CaO-CA catalyst was performed using X-Ray Diffraction (XRD), Thermogravimetric Analysis (TGA), and Surface Area Analyzer (SAA) using the Brunauer-Emmett-Teller (BET) method. This was followed by an esterification-transesterification process with varying times of 4, 5, 6, 7, and 8 minutes at a power of 600 watts. The results of the ZnO/CaO-CA catalyst characterization analysis in the XRD analysis of the single CaO catalyst and the ZnO/CaO-CA catalyst at 2θ were 2θ = 32.22°, 37.98°, and 53.20°, and 2θ = 31.75°, 34.43°, and 36.24°, respectively. The TGA analysis results showed thermal stability with a midpoint at 271.82℃. The SAA analysis results using the BET method showed a surface area of 5.0919 m²/g, a pore volume of 17.6×10⁻³, and a pore diameter of 22.1270 nm. Biodiesel characterization was performed on the transesterification product at the optimal time of 5 minutes using FTIR and GCMS. FTIR analysis revealed the functional groups of methyl esters, namely the methyl group (C-H) and ester groups (C-O), (C=O). GC-MS analysis identified the optimal biodiesel components as octanoic acid (3.07%), decanoic acid (5.81%), dodecanoic acid (20.48%), methyl tetradecanoate (21.33%), and hexadecanoic acid (17.50%).